KETERAMPILAN PROSES SAINS DARI MODEL PEMBELAJARAN KOOPERATIF STAD DAN NHT - Happy Komikesari; I Dewa Putu Nyeneng; Abdurrahman - (Jurnal Pembelajaran Fisika, 2012)
Difficulty understanding the concept of physics because of the material presented and students are less involved in the learning process. This is experienced by students in particular SMA 15 Bandarlampung class X. The purpose of this study to determine the average difference in learning outcomes and cognitive aspects of KPS students in learning physics using a model of cooperative learning type STAD and NHT. The research at SMA Negeri 15 Bandarlampung in classes X4 and X5. Design of experiments in this study using a form of experimentation with the type of Quasi One-Group Pretest-posttest design. Learn the techniques of data analysis using the normalized gain scores and hypothesis testing using the Independent Sample t Test, whereas data analysis using data KPS score observations on the process of learning and hypothesis testing using the test Independent Sample t Test. From this research it brings there are difference in average KPS and student’s studying result between model cooperative learning type STAD and NHT. The average KPS and student’s studying result with type STAD is higher than NHT.Key words: cooperative learning type STAD, NHT, KPS, student’s studyingResult